Niepodległość . miesięcznik polityczny Liberalno-Demokratycznej Partii "Niepoległość", no. 36, 1984 - Kowalski, Józef (s.n.], 1984)
Creation and circulation: Some issues published in 30 cm. and 21 cm. format. Part of the print run in 1983 and 1984 printed in Kraków.